Combination Letrozole and Clomiphene Citrate or Letrozole Alone for Ovulation Induction in Infertile Women with Polycystic Ovarian Syndrome: Letrozole and Clomiphene Citrate or Letrozole Alone for Ovulation Induction with PCOS - Tabassum, Shagufta; Aziz, Amna; Ali, Syeda; Suman, Faiza; Tarin, Ayesha Uzaima (Pakistan Journal of Health Sciences, 2025)
Infertility is a devastating health issue with widespread psychological effects. The most common reason for female infertility is polycystic ovary syndrome. The treatment revolves around Clomophene Citrate (CC) and Letrozole individually, but the combination has not been studied in our population. Objectives: To find if the combination of CC and Letrozole has better ovulation efficacy as compared to Letrozole alone. Methods: The foregoing quasi-experimental study was organized in the Department of Gynaecology at Nishtar Hospital of Pakistan. A total of 70 participants fulfilling the inclusion criteria were divided into two equal groups. Group A was prescribed 2.5 mg Letrozole daily, while Group B was given the composite 2.5 mg letrozole + 50 mg CC per day from the 3rd to the 7th cycle day for one treatment cycle. Results: The combination group yielded ovulation in 65.7% infertile women, while Letrozole alone in 37.1 % of the cases, making a net difference of 28.6% which is quite significant. The conception was achieved in 17.1% of the combination group cases and 14.2% of the Letrozole alone group, making a net difference of 2.9%. The clinical pregnancy was diagnosed in 14.2% of the combination group cases and 11.1% of the Letrozole alone cases, with a net difference of 3.1%. Conclusions: Our findings endorsed the hypothesis that using combined CC + Letrozole leads to a better ovulation rate than Letrozole alone in women experiencing infertility due to polycystic ovary syndrome (PCOS).